Comparative Analysis of Prioritization Model Between AHP (Analytic Hierarchy Process) and ANP (Analytic Network Process) for Project Portfolio Management SI/IT Surabaya City Government - Sari, Rita; Ima Kurniastuti; Endang Sulistiyani (TEKNOLOGI DITERAPKAN DAN JURNAL SAINS KOMPUTER, 2023)
The rapid development of technology to meet the growing demands of projects, particularly in public administration organizations like e-government, faces various resource constraints. Selecting among dozens or even hundreds of alternative projects and portfolios, while aligning with organizational priorities, presents a complex multi-criteria decision-making challenge. This study explores the use of previous research and IS/IT portfolio management techniques to examine project prioritization practices and methods within successful city-level applications. The study further develops a prioritization model by comparing the Analytic Hierarchy Process (AHP) and Analytic Network Process (ANP) methods. The priority levels of nodes (elements) and clusters obtained from the AHP and ANP analyses show relatively insignificant differences; however, the normalized values (eigenvectors) derived from the ANP approach more realistically reflect existing realities. The ANP model offers the advantage of building connections between elements and clusters, enabling feedback analysis, and is considered more effective in bridging the gap between the model and real-world decision-making.